Byzantium in dialogue with the Mediterranean
1 online resource.
Keywords: In thirteen contributions, Byzantium in Dialogue with the Mediterranean. History and Heritage shows that throughout the centuries of its existence, Byzantium continuously communicated with other cultures and societies on the European continent, as well as North Africa and in the East. In this volume, ‘History’ represents not only the chronological, geographical and narrative background of the historical reality of Byzantium, but it also stands for an all-inclusive scholarly approach to the Byzantine world that transcends the boundaries of traditionally separate disciplines such as history, art history or archaeology. The second notion, ‘Heritage’, refers to both material remains and immaterial traditions, and traces that have survived or have been appropriated. Contributors are Hans Bloemsma, Elena Boeck, Averil Cameron, Elsa Fernandes Cardoso, Cristian Caselli, Evangelos Chrysos, Konstantinos Chryssogelos, Penelope Mougoyianni, Daphne Penna, Marko Petrak, Matthew Savage, Daniëlle Slootjes, Karen Stock, Alex Rodriguez Suarez and Mariëtte Verhoeven.